Modelagem geológica e geofísica tridimensional de reservatórios: exemplo de um campo petrolífero da bacia potiguar (NE do Brasil) - Costa, Patrícia Rose de Carvalho (2010)
The geological reservoir modelling, considered an important step to the understanding of oil fields, comprises the description of the characteristics of the oil-bearing poro-perm systems allowing, among otherthings: (i) to construct an integrated framework of all available data; (ii) to assess the needs of acquiring new data; (iii) to quantify volumes of hydrocarbons; (iv) to assist in the location of new wells, and (v) to support the flow simulation and thus to define better inferences about reservoir performance. In this context, this thesis presents the various steps involved in building a three- dimensional geological model of a reservoir from an oil field of Potiguar Basin. The steps consisted, first, by the well data analysis, followed by seismic data analysis and, finally, by the geological modelling itself. During the well data analysis it was performed the quality control analysis of the logs aiming the exclusion of spurious values; stratigraphic correlation between wells with interpretation of basin units and hydrocarbon reservoir zones; analysis of petrophysical and core data, and characterization of electrofacies for the reservoirs. During the seismic data analysis, it was carried out the correlation between wells (depth range) and seismics (time scale); seismic interpretation of regional horizons; seismic inversion to improve the data quality; creation of a velocity model for data conversion from time to depth; seismic interpretation of the reservoir zones defining their top and bottom horizons, and seismic attributes analysis. The research culminated with the construction of the structural model, followed by facies and petrophysical models (porosity and permeability) and, finally, with the oil volume calculation for the reservoir zones and uncertainty analysis of the calculated volumes.